IMPLEMENTASI PROGRAM AKSI POTENSI DALAM MENINGKATKAN KECERDASAN VERBAL LINGUISTIK SISWI DI MADRASAH ALIYAH PERGURUAN MU’ALLIMAT QUR’ANI CUKIR JOMBANG - Nadia Putri; Aida Arini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Communication is one of the intelligences possessed by humans. It falls under verbal-linguistic intelligence, which can serve as a means for individuals to develop language and communication skills. This study aims to identify and analyze the Speech Potential Action Program in enhancing the verbal-linguistic intelligence of female students at MA Perguruan Mu’allimat Cukir Jombang. A qualitative approach with a case study method based on field data and observed behavior was employed. Data collection techniques included observation, interviews, and documentation. The informants in this study consisted of the head of the madrasa, the vice principal for curriculum, the supervisor of the speech potential action program, and students of MA Perguruan Mu’allimat Cukir Jombang. The implementation of the Speech Potential Action Program in improving the students’ verbal-linguistic intelligence included activities such as classifying students, organizing a speech schedule, preparing speech themes, and watching YouTube videos to enrich their speech styles.